Pengaruh Gadget Terhadap Kemampuan Interaksi Sosial Siswa Sekolah Dasar - Rini Budiwati; Murfiah Dewi Wulandari; Darsinah Darsinah (Peneliti.net, 2022)
Technological advances are increasingly complex and evolving. This has various implications on human life, including mentality and behavior. Gadgets are one of the technical innovations that have an impact on the human mind. Gadgets are electronic devices used for modern communication. In Indonesia, most children spend their time playing with electronic devices. Of course this has an impact on children's development, especially in terms of social interaction. The term